Synthesis and Optoelectronic Characteristics of MGdAl3O7:Eu3+ Nanophosphors for Current Display Devices. Issue 4 (2nd October 2019) - Kadyan, Sonika; Singh, Sitender; Sheoran, Suman; Samantilleke, Anura; Mari, Bernabe; Singh, Devender
Abstract : Novel Eu 3+ doped MGdAl3 O7 (M = Mg, Ca, Sr and Ba) phosphors were synthesized and examined. The samples were prepared at 600°C using solution-combustion procedure and investigated at 0.01 to 0.05 mole of dopant ion concentration. The optimal concentration of Eu 3+ ions was 0.03 mole for MGdAl3 O7 host matrix. On 393 nm excitation, the materials exhibited sharp red emission at 608-614 nm because of 5 D0 → 7 F2 (electric dipole allowed) transition. Structural and phase purity of the materials were determined by X-ray diffraction (XRD) analysis. XRD patterns of the phosphors exhibited single-phase tetragonal structure with P 421 m space group. Significant rise in the luminous intensity and crystallinity of the materials was observed with increase in temperature. Shape and size of the crystallites were confirmed by transmission electron microscopy (TEM). TEM image displayed spherical crystallites of 14-30 nm size. FTIR spectra of CaGdAl3 O7 exhibited various stretching modes at 455, 699 and 776 cm –1 comparable to Ca-O, Gd-O and Al-O. Eu 3+ doped MGdAl3 O7 could be brilliant materials for applications in white light-emitting diodes, fluorescent panels and modern display devices. GRAPHICAL ABSTRACT: